2016
DOI: 10.1039/c6nj00098c
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of colloidal copper xanthate nanoparticles

Abstract: Colloids formed by the direct interaction of aqueous Cu2+ ions and xanthates were characterized along with their precipitates incorporating dixanthogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 44 publications
(68 reference statements)
0
6
0
3
Order By: Relevance
“…UV spectra obtained for samples at the same concentration confirmed the occurrence of dithiocarbonate groups at the end of the polymer chains (Supplementary Figure SI8). The absorption band at 280 nm related to the ππ* transition of the OC(S)S moiety 28,29 was present in the UV spectra of all samples. As expected, the intensity of this band was reduced with increased chain length.…”
Section: Synthesis and Characterization Of Chol-pnipaam-x Polymersmentioning
confidence: 92%
“…UV spectra obtained for samples at the same concentration confirmed the occurrence of dithiocarbonate groups at the end of the polymer chains (Supplementary Figure SI8). The absorption band at 280 nm related to the ππ* transition of the OC(S)S moiety 28,29 was present in the UV spectra of all samples. As expected, the intensity of this band was reduced with increased chain length.…”
Section: Synthesis and Characterization Of Chol-pnipaam-x Polymersmentioning
confidence: 92%
“…4. Микрофотографии (ПЭМ) золей образцов 1-6 и диаграммы распределения частиц по размерам и 6 максимум сдвинут к более высоким энергиям около 932,8 эВ, сателлиты "встряски" в об ласти 944-948 эВ отсутствуют, что указывает на медь в степени окисления 1+ [31][32][33]. По ложение Оже-линии CuL 3 MM, как и модифицированный параметр Вагнера (сумма энергий свя зи Cu2p 3/2 и кинетической энергии CuL 3 M 4 5 M 4 5 ) примерно одинаковы для образцов 1-4 (1850,0+0,1 эВ) и заметно отличается для образцов 5 и 6 (1850,4 эВ), по-видимому, из-за вклада комплексов меди, осаждающихся из раствора при большом избытке тиосульфата.…”
Section: результаты и их обсуждениеunclassified
“…По ложение Оже-линии CuL 3 MM, как и модифицированный параметр Вагнера (сумма энергий свя зи Cu2p 3/2 и кинетической энергии CuL 3 M 4 5 M 4 5 ) примерно одинаковы для образцов 1-4 (1850,0+0,1 эВ) и заметно отличается для образцов 5 и 6 (1850,4 эВ), по-видимому, из-за вклада комплексов меди, осаждающихся из раствора при большом избытке тиосульфата. Основная линия спектра S2p может быть разложена на дублеты моносульфида S 2-с максимумом S2p 3/2 при 161 эВ, дисульфида S 2 с энергией связи около 162 эВ и линию с максимумом около 163 эВ, которую следует отнести к полисульфидной форме -продукту окисления поверхности сульфидов меди и/или сере в составе тиосульфата [31,32]. Кроме того, имеется полоса около 166-169 эВ кислородсодержащих анионов, преимущественно сульфата и избыточного тио сульфата натрия, осажденных при высушивании раствора.…”
Section: результаты и их обсуждениеunclassified
“…One century later, Brandenberger synthesized a new polyxanthate called cellophane of cellulose . Continuing such trends, firstly Mikhlin and co‐workers developed a new strategy for producing copper xanthate in colloidal phase and nanoscale size and demonstrated that copper occurs as Cu(I) …”
Section: Introductionmentioning
confidence: 99%